2020
DOI: 10.5194/amt-13-4009-2020
|View full text |Cite
|
Sign up to set email alerts
|

On the performance of satellite-based observations of <i>X</i>CO<sub>2</sub> in capturing the NOAA Carbon Tracker model and ground-based flask observations over Africa's land mass

Abstract: Abstract. Africa is one of the most data-scarce regions as satellite observation at the Equator is limited by cloud cover and there is a very limited number of ground-based measurements. As a result, the use of simulations from models is mandatory to fill this data gap. A comparison of satellite observation with model and available in situ observations will be useful to estimate the performance of satellites in the region. In this study, GOSAT column-averaged carbon dioxide dry-air mole fraction (XCO2) is comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Around Kuwait, the magnitude of the annual cycle is typically 3-4 ± 0.5 ppmv, Figure 3B, in line with that measured in-situ at Kuwait City from June 1996 to May 2001 (Nasrallah et al, 2003). The seasonal cycle amplitude increases to 8-10 ± 1 ppmv at higher latitudes (Keeling et al, 1996) and in southwestern and southeastern parts of the Arabian Peninsula and tropical Africa (Mengistu and Tsidu, 2020), owing to a more marked seasonality of plant activity on top of anthropogenic emissions in particular in the mid-latitudes (Figure 2A). A similar seasonal cycle amplitude is seen over India where the annual maximum occurs in the drier and hotter pre-monsoon months of April to June, and the minimum in the cooler and wetter summer monsoon months of June to September (Kunchala et al, 2022).…”
Section: Co 2 Anthropogenic Emissionssupporting
confidence: 81%
“…Around Kuwait, the magnitude of the annual cycle is typically 3-4 ± 0.5 ppmv, Figure 3B, in line with that measured in-situ at Kuwait City from June 1996 to May 2001 (Nasrallah et al, 2003). The seasonal cycle amplitude increases to 8-10 ± 1 ppmv at higher latitudes (Keeling et al, 1996) and in southwestern and southeastern parts of the Arabian Peninsula and tropical Africa (Mengistu and Tsidu, 2020), owing to a more marked seasonality of plant activity on top of anthropogenic emissions in particular in the mid-latitudes (Figure 2A). A similar seasonal cycle amplitude is seen over India where the annual maximum occurs in the drier and hotter pre-monsoon months of April to June, and the minimum in the cooler and wetter summer monsoon months of June to September (Kunchala et al, 2022).…”
Section: Co 2 Anthropogenic Emissionssupporting
confidence: 81%
“…Previous authors have suggested this may result from the inefficiency of satellite measurements in detecting the canopy activities of tropical forest (Tang and Dubayah, 2017), due to limitations in their retrieval due to atmospheric cloud contamination (Frankenberg et al, 2014;Doughty et al, 2019) or to limitations in the EC measurement technique itself (Hayek et al, 2018). Eddy correlation measurements over rainforests are more complicated than over flat vegetation due to the presence of tall uneven canopies (Mercado et al, 2006) as well as stable atmospheric conditions at night (Miller et al, 2004). This comes on top of the uncertainty incurred on the derived GPP, which requires a partitioning of the measured net ecosystem exchange during turbulent conditions (Reichstein et al, 2005).…”
Section: Discussionmentioning
confidence: 99%